Breast-Feeding Analgesia in Infants: An Update on the Current State of Evidence. Issue 2 (April 2017) - Benoit, Britney; Martin-Misener, Ruth; Latimer, Margot; Campbell-Yeo, Marsha
Abstract : To provide an updated synthesis of the current state of the evidence for the effectiveness of breast-feeding and expressed breast milk feeding in reducing procedural pain in preterm and full-term born infants. A systematic search of key electronic databases (PubMed, CINAHL, EMBASE) was completed. Of the 1032 abstracts screened, 21 were found eligible for inclusion. Fifteen studies reported on the use of breast-feeding or expressed breast milk in full-term infants and 6 reported on preterm infants. Direct breast-feeding was more effective than maternal holding, maternal skin-to-skin contact, topical anesthetics, and music therapy, and was as or more effective than sweet tasting solutions in full-term infants. Expressed breast milk was not consistently found to reduce pain response in full-term or preterm infants. Studies generally had moderate to high risk of bias. There is sufficient evidence to recommend direct breast-feeding for procedural pain management in full-term infants. Based on current evidence, expressed breast milk alone should not be considered an adequate intervention.